Ensino de ciências na escola do campo em alternância : o caso de uma escola do município de Terra Nova do Norte em Mato Grosso - Oliveira, Valdenor Santos (2012)
This study presents an investigation on the teaching of science at the Escola Estadual de Educação Básica Terra Nova, a school in a rural area, that uses Pedagogy of Alternation in Terra Nova do Norte located in the State of Mato Grosso. Aims to understand as they have done science teaching at this school, from the political and pedagogical proposal and the prospects of students, parents and teachers, establishing a relationship between what is proposed in the Pedagogical Political Project (PPP) and the pedagogical actions in the teaching of sciences. The research is of a qualitative approach, developed through a case study which, in the explorative phase, happened in the place of research with the presentation of the proposal to the management of the school and with the selection of bibliography that would permit a better understanding of the problem. In the period of data collection observations were made as well as a documental analysis of the PPP, making possible the elaboration of the history of the creation of the school, the understanding of the agro-ecology course and its curriculum, and offered elements to elaborate a semi-structured interview with five students, representatives of their groups in the Deliberative Counsel of the School Community, and one teacher of natural sciences, mathematics and technologies. The analysis of the data was made from the triangulation of the information obtained in the observation, the study of the PPP and the systematization of the interviews for which were established four criteria of analysis being: time and space of the pedagogy of alternation in the process of teaching and learning of science, the perspectives of social transformation attributed to the teaching of science, the planning of activities in the teaching of sciences, and the teaching methodologies and strategies used by the teacher in science classes. It became evident that the teaching of sciences at the Escola Estadual de Educação Básica Terra Nova has suffered uncountable changes that have tried to offer its students a better understanding of the sciences from a point of view of the social-historical circumstances of society, respecting their specificities and ways of reading the world. It is an educational project that guarantees an integral formation, involving intellectual and social aspects, qualifying them to continue their studies or to take on immediately the role of entrepreneur of the family property, or any other.